A Phosphino Calix[4]arene Bis‐Frustrated Lewis Pair. Issue 8 (31st January 2014) - Arnott, Gareth E.; Moquist, Philip; Daniliuc, Constantin G.; Kehr, Gerald; Erker, Gerhard
Abstract: A bis‐frustrated Lewis pair based on a calix[4]arene skeleton is reported for the first time. Importantly, this system has been shown to activate two molecules of hydrogen, thereby establishing a proof of concept for multisite frustrated Lewis pair (FLP) design and synthesis. The complex [calixarene‐(Mes2 PH + )2 ][BH(C6 F5 )3 – ]2 (6 ) has been characterised by X‐ray crystal structure analysis. Abstract : The synthesis and X‐ray structure of a calix[4]arene bis‐frustrated Lewis pair is described for the first time. This compound is the first example of a frustrated Lewis pair system capable of doubly activating H2 as well as the first use of a calixarene in frustrated Lewis pair chemistry.